2017
DOI: 10.1016/j.ebiom.2017.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Batf3-dependent CD8α + Dendritic Cells Aggravates Atherosclerosis via Th1 Cell Induction and Enhanced CCL5 Expression in Plaque Macrophages

Abstract: Dendritic cells (DCs) play an important role in controlling T cell-mediated adaptive immunity in atherogenesis. However, the role of the basic leucine zipper transcription factor, ATF-like 3 (Batf3)-dependent CD8α+ DC subset in atherogenesis remains unclear. Here we show that Batf3−/− Apoe−/− mice, lacking CD8α+ DCs, exhibited a significant reduction in atherogenesis and T help 1 (Th1) cells compared with Apoe−/− controls. Then, we found that CD8α+ DCs preferentially induce Th1 cells via secreting interleukin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 53 publications
(94 reference statements)
2
27
0
Order By: Relevance
“…Collectively, these data of CD103 + DC in other tissues lead to a hypothesis that vascular CD103 + DCs could also induce Treg differentiation and recruitment in early atherosclerotic lesions via TGF-β/retinoic acid or CCL22 pathways, respectively, which agrees with previous reports that vascular CD103 + DCs protect against atherosclerosis via Tregs (18). However, when the atherogenic roles of CD103 + DCs were assessed in mice deficient in their dependent transcription factor Batf3 in ApoE −/− mice, which also lacked CD103 + DCs, a significant reduction in atherogenesis via reduced Th1 cell induction and C-C motif ligand 5 (CCL5) expression were found (20), whereas mice deficient in the same transcription factor but crossed with Ldlr −/− mice demonstrated mild effects on the immune response in the spleen without altering atherosclerotic lesion formation and plaque phenotype (37). These conflicting results could be caused by different model specific pathologies in the development of atherosclerosis.…”
Section: Cd103 + Dcs In Atherosclerosissupporting
confidence: 90%
“…Collectively, these data of CD103 + DC in other tissues lead to a hypothesis that vascular CD103 + DCs could also induce Treg differentiation and recruitment in early atherosclerotic lesions via TGF-β/retinoic acid or CCL22 pathways, respectively, which agrees with previous reports that vascular CD103 + DCs protect against atherosclerosis via Tregs (18). However, when the atherogenic roles of CD103 + DCs were assessed in mice deficient in their dependent transcription factor Batf3 in ApoE −/− mice, which also lacked CD103 + DCs, a significant reduction in atherogenesis via reduced Th1 cell induction and C-C motif ligand 5 (CCL5) expression were found (20), whereas mice deficient in the same transcription factor but crossed with Ldlr −/− mice demonstrated mild effects on the immune response in the spleen without altering atherosclerotic lesion formation and plaque phenotype (37). These conflicting results could be caused by different model specific pathologies in the development of atherosclerosis.…”
Section: Cd103 + Dcs In Atherosclerosissupporting
confidence: 90%
“…The expansion of CD11c + APCs has previously been linked to an atheroprotective decrease in plasma cholesterol levels [ 7 ]. We did not observe any differences in serum lipids between Ldlr -/- Batf3 -/- and Ldlr -/- mice fed a high fat diet, implying that Batf3-dependent cells are not involved in cholesterol metabolism, in line with findings in chimeric Ldlr -/- mice reconstituted with Batf3 -/- bone marrow [ 12 ], Flt3 -/- Ldlr -/- mice that lack CD103 + DCs in the aorta [ 14 ] and in an ApoE -/- Batf3 -/- mouse model [ 13 ].…”
Section: Discussionsupporting
confidence: 69%
“…In another study using ApoE -/- Batf3 -/- a decreased plaque size was reported after 12 weeks of HFD without alterations in Treg numbers [ 13 ]. The authors have suggested that Batf3-dependent DCs might exert their proatherogenic role via induction of Th1 responses, mainly affecting IFNγ release, which affected CCL5 secretion by macrophages, a chemokine known to promote leukocyte recruitment in plaque [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, RANTES also promotes atherogenesis by inducing the accumulation of inflammatory cells , probably through a T‐helper 1 cell response . In fact, treatment with an antagonist of the RANTES receptor inhibits recruitment of T cells and macrophages into the plaque area and alleviates atherosclerosis .…”
Section: Discussionmentioning
confidence: 99%